Focusing surface phonon-polaritons for tunable thermal radiation - Jose Ordonez-Miranda; Masahiro Nomura; Sebastian Volz (Discover Nano)
Abstract We demonstrate unprecedented control and enhancement of thermal radiation using subwavelength conical membranes of silicon nitride. Based on fluctuational electrodynamics, we find that the focusing of surface phonon-polaritons along these membranes enhances their far-field thermal conductance by three orders of magnitude over the blackbody limit. Our calculations reveal a non-monotonic dependence of the thermal conductance on membrane geometry, with a characteristic radiation plateau emerging at small front widths due to competing effects of the polariton focusing and radiative area. The obtained results thus introduce the conical geometry as a powerful degree of freedom for tailoring thermal radiation, with potential implications for energy harvesting and thermal management at the nanoscale.